Autoantibodies Against Albumin in Patients With Systemic Lupus Erythematosus - Nehring, Josephine; Schirmbeck, Lucia A.; Friebus-Kardash, Justa; Dubler, Denise; Huynh-Do, Uyen; Chizzolini, Carlo; Ribi, Camillo; Trendelenburg, Marten (Frontiers in Immunology, 2018)
Objectives: Autoantibodies and aberrant immune complexes are pathological hallmarks of systemic lupus erythematosus (SLE). This study aimed to determine the occurrence of IgG autoantibodies against human serum albumin (anti-HSA) and their potential association with antibodies against bovine serum albumin (anti-BSA) in patients with SLE. Methods: Sera of 180 SLE patients included to the Swiss SLE Cohort Study and 188 age- and sex-matched healthy controls were evaluated. Levels of anti-HSA IgG and anti-BSA IgG were quantified by ELISA. Selected samples were further characterized using serum fractions obtained by fast liquid chromatography (FPLC). Results: SLE patients had increased levels of anti-HSA (p=0.002) but similar levels of anti-BSA IgG compared with matched healthy controls. Anti-HSA IgG levels correlated with the SLE Disease Activity Index (SLEDAI), which was more pronounced in patients with an physician’s global assessment (PGA) of ≥ 1 (r=0.309, p=0.0066). Anti-HSA IgG were partially complexed with serum albumin but also occurred as monomeric autoantibodies in highly positive SLE patients. A positive correlation between anti-HSA IgG and anti-BSA IgG was found that was stronger in SLE patients than in healthy controls (r=0.3172, p<0.001 vs. r=0.2122, p<0.0035). Binding of anti-BSA IgG was inhibited partially in the presence of HSA in samples with double positivity for anti-HSA and anti-BSA (median inhibition 47.9%, range 0.9-100 %) and vice versa. Conclusions: SLE patients were found to have an increased prevalence of anti-HSA antibodies that are associated with SLE disease activity, and with the occurrence of anti-BSA antibodies, suggesting food-derived bovine albumin as a trigger.